1988
DOI: 10.18474/0749-8004-23.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Host Monoterpenes to Dendroctonus Frontalis and Ips Calligraphus (Coleoptera: Scolytidae)

Abstract: The toxicity of four monoterpenes present in loblolly (Pinus taeda L.) and shortleaf (P. echinata Mill.) pine to Dendroctonus frontalis Zimmermann and Ips calligraphus (Germar) (Coleoptera: Scolytidae) was examined in the laboratory. The descending order of toxicity of the monoterpenes to D. frontalis was: limonene, β - pinene, α - pinene, camphene. No clearcut ordering in toxicity to I. calligraphus was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…It may also communicate the defensive capabilities of the potential host, as has been suggested to occur for less aggressive bark beetle species that are attracted to modest concentrations of host monoterpenes but repelled by higher ones (Erbilgin et al, 2003). Host monoterpenes are toxic to bark beetles (Cook and Hain, 1988;Everaerts et al, 2012), and presumably airborne resin terpene concentrations that exceed a certain threshold should signal a host whose defensive response may be greater than can be withstood by the host-seeking species (Erbilgin et al, 2007b). The very high rates of turpentine odours preferred by D. frontalis are simultaneously inhibitory to their significant competitor I. avulsus (Billings, 1985).…”
Section: Host Monoterpenesmentioning
confidence: 99%
“…It may also communicate the defensive capabilities of the potential host, as has been suggested to occur for less aggressive bark beetle species that are attracted to modest concentrations of host monoterpenes but repelled by higher ones (Erbilgin et al, 2003). Host monoterpenes are toxic to bark beetles (Cook and Hain, 1988;Everaerts et al, 2012), and presumably airborne resin terpene concentrations that exceed a certain threshold should signal a host whose defensive response may be greater than can be withstood by the host-seeking species (Erbilgin et al, 2007b). The very high rates of turpentine odours preferred by D. frontalis are simultaneously inhibitory to their significant competitor I. avulsus (Billings, 1985).…”
Section: Host Monoterpenesmentioning
confidence: 99%
“…Fordyce and Malcolm (2000) showed that the piths of milkweeds contained nonpolar cardenolids that may be particularly toxic against the larvae of the milkweed weevil R. lineaticollis. Other studies have found stemassociated terpenoids to function as feeding deterrents or repellants (Nordlander, 1990;Lindgren et al, 1996) or toxins (Cook and Hain, 1988;Raffa and Smalley, 1995;Werner, 1995) to bark beetles and pine weevils.…”
mentioning
confidence: 99%
“…Studies investigating toxicity of individual components of many EO are generally limited to invertebrate herbivores; relatively few focus on vertebrates. In studies of invertebrate herbivores, camphene was shown to be among the least toxic EO terpenoids (Cook and Hain 1988;Abdelgaleil et al 2009). Camphene-specific effects on vertebrate herbivores are poorly understood.…”
Section: Discussionmentioning
confidence: 99%